Efektivitas Serbuk Biji Pinang (Areca catechu L.) dalam Mengendalikan Kumbang Beras (Sitophilus oryzae L.) di Penyimpanan: Effectiveness of Areca Nut (Areca catechu L.) Seed Powder for Controlling Rice Weevil (Sitophilus oryzae L.) Infestation in Storage - Fitriana, Melani; Desita Salbiah (UIR Press, 2026)
Background: Rice (Oryza sativa L) is the primary staple food in Indonesia, but its quality is frequently compromised during storage by the rice weevil (Sitophilus oryzae L.) Objective: This study aimed to evaluate the efficacy of areca nut (Areca catechu L.) seed powder as a botanical insecticide to control S. oryzae infestations. Methods: The study was conducted experimentally using a completely randomized design with 5 treatments and 4 replications. The study consisted of two series, the first series included 20 experimental units for observing time to initial mortality and total mortality, while the second series included 20 experimental units for observing population growth and rice weight loss. The doses of areca nut seed powder used for each experimental unit 0 g.100 rice, 2.5 g.100 rice, 5 g.100 rice, 7.5 g.100 rice, and 10 g.100 rice. Results: The results showed that a dose of 10 g.100 rice was the most effective for controlling S. oryzae, causing a total mortality of 82.5% with an initial mortality time of 28.25 hours after application. The 10 g.100 rice also resulted in the lowest rice weight loss percentage of 0.95% and the least population increase 3.25 individuals. Conclusions: In conclution, a dosage of 10 g.100 rice is the most effective dosage of areca nut seed powder for controlling S. oryzae